(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Comorbidities of migraine patients are not uncommon. Objective: This study was done to find out sociodemographic characteristics and the important comorbid psychiatric and physical illness in migraine patients. Methodology: This cross sectional study was carried out in the Neurology Outdoor and Headache Clinic at Dhaka Medical College Hospital, Dhaka from July 2010 to June 2011 for a period of 1 year. Patients with migraine (on the basis of International headache society migraine headache criteria), age ≥16 years with total duration of headache six months or more, having comorbidities like major depressive disorder (MDD), generalized anxiety disorder (GAD), hypertension (HTN), diabetes mellitus (DM) or obesity were included in the study (n=33).The sociodemographic and relevant data were collected in a preformed data sheet from each patient. Result: The mean age of the participants was 33.8±8.8 years. Most of them were in 31-40 year age group (39.4%), followed by 21-30 year age group (36.4%). Most of the participants were female (72.7%) and housewives (57.6%). The symptoms of migraine was severe according to Migraine Severity Scale (MIGSEV) in 19 (57.6%), moderate in 8 (24.2%) and mild in 6 (18.2%) participants. Among the comorbidities, psychiatric problems like GAD and MDD was present in 8 (24.2%) and 6 (18.2%) participants respectively. Seven (21.2%) were obese, 4 (12.1%) hypertensive and 8 (24.2%) diabetic. Frequency of headache/month was observed to be higher in participants with hypertension (5.0±1.4 episodes/month) and duration of episodic migraine headache was higher in those with MDD (23.4±10.3 hours). Conclusion: Patients of migraine have comorbidities like GAD, MDD, obesity, hypertension and DM which need to be addressed appropriately for proper migraine headache management. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 48-51